Zinc impregnation agent, zinc impregnation method of electric power connection fitting and anti-corrosion electric power connection fitting

By using specific ingestion agents and optimized processes, a zinc seepage layer with large thickness and high hardness is formed, which solves the problem of thin thickness and low hardness of the surface zinc seepage layer of the power metal in the prior art, and significantly improves corrosion resistance and wear resistance, extending the service life of electric power tools.

CN119457058APending Publication Date: 2025-02-18STEJT GRID ELEKTRIK PAUER INZHINIRING RISERCH INSTITYUT KO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411636567.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, the zinc seepage layer of the power metal is thin and has low hardness, which leads to prone to failure under the composite effect of corrosion and wind and sand wear.

Method used

A zinc permeable agent containing 54.0-57.0% zinc powder, 20.0-23.0% SiO2 powder, 3.0-3.5% CeO2 powder and other components are used to form a large thickness and high hardness through austenitization treatment and a staged cooling process. Zinc permeable layer.

Benefits of technology

The thickness of the surface zinc seepage layer of the power metal is achieved to reach 162-171 µm and the hardness is 483-505 HV, which significantly improves corrosion resistance and wear resistance and extends the service life of the power metal.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a zinc impregnation agent, a zinc impregnation method of an electric power connection fitting and an anti-corrosion electric power connection fitting. A steel fitting is austenitized and then cooled; the surface of the cooled steel fitting is pretreated; and the pretreated steel fitting and a zinc impregnation agent are added into a closed impregnation tank, heat preservation is conducted at the set temperature, and then staged cooling is conducted. The zinc impregnation agent is prepared from the following components in percentage by mass: 54.0 percent to 57.0 percent of zinc powder, 20.0 percent to 23.0 percent of SiO2 powder, 3.0 percent to 3.5 percent of CeO2 powder, 5.0 percent to 6.0 percent of aluminum powder, 2.5 percent to 3.0 percent of nickel powder, 2.5 percent to 3.0 percent of chromium powder, 3.0 percent to 3.5 percent of magnesium powder, 2.5 percent to 2.8 percent of NH4Cl powder and 2.5 percent to 3.0 percent of B4C powder. The thickness of a zinc impregnation layer is larger than 160 m, and the hardness of the zinc impregnation layer is larger than 480 HV; and the sherardizing layer is compact in structure, and the sherardizing layer is well combined with the surface of the 35CrMo steel fitting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface treatment, and relates to a surface treatment method for an electric connection fitting, and in particular to a sherardizing agent, a sherardizing method for an electric connection fitting, and an anti-corrosion electric connection fitting. Background Art

[0002] Due to the relatively harsh working environment of the transmission line, the power connection fittings are easily damaged by atmospheric corrosion and wind and sand wear, which will cause great safety hazards to the transmission line. At the same time, it is difficult to replace the connection fittings, and frequent replacement will cause a lot of waste of manpower and financial resources. Therefore, it is very important to perform surface treatment on the transmission line connection fittings to improve their corrosion resistance and wear resistance.

[0003] In order to improve the corrosion resistance and wear resistance of power connection fittings for transmission lines, Chinese invention patent CN111926285A discloses a method for preparing zinc-aluminum-magnesium powder sherardizing agent and using it for steel processing. The raw materials used are 30% to 60% zinc powder, 20% to 40% 5083 magnesium-aluminum alloy powder, 1% to 3% ammonium chloride, and the balance is alumina by weight percentage. The composition of 5083 magnesium-aluminum alloy powder is: 4.0 to 4.9% Mg, 93% to 96% Al, and the particle size is 100 to 200 mesh. After the metal substrate is degreased and derusted, it is sherardized in a vacuum environment, with an annealing temperature of 420 to 470°C and a time of 3 to 5 hours. After cooling, the sherardized substrate is passivated, and the hardness of the sherardized layer is 278.92 HV, and the depth of the sherardized layer can reach 65 μm.

[0004] The above patent adopts the zinc-diffusion technology. Although the zinc-diffusion layer has good corrosion resistance, it is still thin and has low hardness. As a result, the surface of the power fittings is very likely to fail under the combined effects of corrosion and wind and sand wear after ordinary zinc-diffusion treatment. Summary of the invention

[0005] In order to overcome the technical problems of thin thickness and low hardness of the zinc-plating layer on the surface of electric fittings in the prior art, the purpose of the present invention is to provide a zinc-plating agent, a zinc-plating method for electric connection fittings and an anti-corrosion electric connection fitting, which can obtain a zinc-plating layer with large thickness and high hardness on the surface of the electric fittings, thereby achieving the goal of extending the service life of the electric fittings.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A zincizing agent comprises, by mass percentage, 54.0-57.0% zinc powder, 20.0-23.0% SiO2 powder, 3.0-3.5% CeO2 powder, 5.0-6.0% aluminum powder, 2.5-3.0% nickel powder, 2.5-3.0% chromium powder, 3.0-3.5% magnesium powder, 2.5-2.8% NH4Cl powder and 2.5-3.0% B4C powder.

[0007] A further improvement of the present invention is that the particle size of the zinc powder, SiO2 powder, magnesium powder, NH4Cl powder, nickel powder, chromium powder and B4C powder is 80-120 mesh.

[0008] A further improvement of the present invention is that the size of CeO2 powder and aluminum powder is 50-80 nm.

[0009] A method for sherardizing an electric power connection fitting comprises the following steps: The steel fittings are austenitized and then cooled; Pre-treating the surface of the cooled steel fittings; The pretreated steel fittings and the zincizing agent are added into a closed infiltration tank, kept warm at the set temperature, and then cooled in stages.

[0010] A further improvement of the present invention is that the austenitizing temperature is 830-850° C. and the time is 30-45 minutes.

[0011] A further improvement of the present invention is that the steel fittings are cooled by oil quenching after being austenitized.

[0012] A further improvement of the present invention is that the set temperature is 410-415°C and the holding time is 1.5-2.0 h.

[0013] A further improvement of the present invention is that the temperature is increased to the set temperature at a heating rate of 60-80°C / h.

[0014] A further improvement of the present invention is that the staged cooling is specifically: first at 350-360°C, keep warm for 7-8 hours, then cool to 180-200°C with the furnace, and then naturally cool to room temperature.

[0015] A further improvement of the present invention is that the surface of the cooled steel fitting is pretreated, including degreasing and rust removal.

[0016] The invention discloses an anti-corrosion electric power connection fitting, which is made by adopting a zinc infiltration method for the electric power connection fitting.

[0017] A further improvement of the present invention is that it comprises an electric power connection fitting and a sherardizing layer on the surface of the electric power connection fitting, wherein the thickness of the sherardizing layer is 162-171 μm and the hardness of the sherardizing layer is 483-505 HV.

[0018] Compared with the prior art, the present invention has the following beneficial effects: The CeO2 powder contained in the sherardizing agent of the present invention can accelerate the penetration of zinc element into the surface of 35CrMo steel hardware, increase the thickness of the sherardizing layer and the hardness of the sherardizing layer, and can also improve the corrosion resistance of the sherardizing layer. The aluminum powder, nickel powder, chromium powder and magnesium powder in the sherardizing agent can further improve the corrosion resistance of the sherardizing layer. The B4C powder and chromium powder in the sherardizing agent are easy to generate a high-hardness Cr2B phase in the sherardizing layer, thereby improving the hardness and wear resistance of the sherardizing layer. The high-melting-point SiO2 powder is added to the sherardizing agent, the main function of which is to prevent the zinc powder from bonding with the surface of the 35CrMo steel hardware during the sherardizing process. The NH4Cl powder in the sherardizing agent, as an activator, mainly activates the zinc and the surface of the 35CrMo steel hardware to promote the sherardizing process.

[0019] In order to ensure the thickness of the sherardizing layer, the present invention adopts staged cooling to eliminate the internal stress of oil-cooling quenching of steel hardware, stabilize the structure, and improve the toughness and plasticity of steel hardware. The sherardizing time of the present invention is short, the thickness of the sherardizing layer is greater than 160 µm, and the hardness of the sherardizing layer is greater than 480 HV; the sherardizing layer has a dense structure, and the sherardizing layer is well bonded to the surface of the 35CrMo steel hardware, ensuring that the sherardizing layer will not crack or peel off during the use of the hardware, overcoming the problems of unstable sherardizing layer and long process cycle in traditional powder sherardizing technology. The sherardizing process of the present invention has no air pollution, no zinc vapor pollution, no zinc dust pollution, no acid water pollution, and no chromium water pollution, and is a clean sherardizing technology.

[0020] Furthermore, in the sherardizing agent of the present invention, by adding nano-scale CeO2, the penetration of zinc element into the surface of steel hardware is accelerated, the sherardizing temperature is reduced, the sherardizing time is shortened, and good energy-saving effect is achieved. The problem that in traditional sherardizing, in order to increase the thickness of the sherardizing layer, it is necessary to increase the sherardizing temperature to above 420°C, which exceeds the melting point of zinc and is in liquid phase, accelerates the penetration of liquid zinc into the metal surface, and obtains the desired sherardizing layer, but the sherardizing agent is easy to adhere to the metal surface and is not easy to clean, is overcome.

[0021] Furthermore, since NH4Cl in the sherardizing agent is easily decomposed by heat, the generated hydrogen chloride gas and ammonia gas will overflow from the closed infiltration tank, making the sherardizing agent loose. When the gas overflows, the air outside the tank will enter the tank, causing oxidation of the surface of the steel fittings and the sherardizing agent. The pretreated steel fittings and the sherardizing agent of the present invention are added to the closed infiltration tank, heated to the set temperature of 410-415℃, and the heating rate is controlled at 60-80℃ / h. The heating rate is slow, and the ammonium chloride (NH4Cl) decomposes slowly, so the expected reducing atmosphere will not be destroyed. At the same time, the gas generated by the decomposition of ammonium chloride will squeeze the air in the tank out of the closed infiltration tank, which can ensure that the surface of the fittings will not be oxidized. Since the melting point of zinc is low, only 419.5℃, the high temperature insulation time of sherardizing is too long, zinc is easy to melt, and adheres to the surface of the steel fittings, which seriously affects the surface quality of the fittings. Therefore, the insulation time of the set temperature is controlled at 1.5-2.0h.

[0022] The zinc-plated layer of the anti-corrosion power connection fittings of the present invention has high hardness and excellent corrosion and wear resistance, and the corrosion and wear resistance of the zinc-plated layer is more than 80% higher than that of the ordinary zinc-plated layer and more than 3 times higher than that of the quenched 35CrMo steel. The present invention can significantly extend the service life of the power fittings and has a good prospect for promotion and application. DETAILED DESCRIPTION

[0023] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below. However, the present invention can be implemented in a variety of different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0024] The power connection fittings of the present invention are described by taking 35CrMo steel fittings as an example.

[0025] The zincizing method of a power connection fitting of the present invention has the following specific preparation steps: ① First, heat the 35CrMo steel fittings to 830-850 ℃, keep them warm for 30-45 minutes, and then oil-quench them; among them, keep them warm at 830-850 ℃ for 30-45 minutes to achieve high-temperature austenitization. Oil-quenching can accelerate the cooling of the fittings and obtain a high-strength lath martensite structure.

[0026] Then, the surface of the 35CrMo steel hardware after oil cooling and quenching is pretreated, and the hardware surface pretreatment includes degreasing and rust removal; degreasing is the first step in the pretreatment of 35CrMo steel hardware. In the production process of 35CrMo steel hardware, a layer of grease or dirt often adheres to the surface of 35CrMo steel hardware, which will affect the effect of subsequent zinc infiltration. Therefore, in the pretreatment process, it is necessary to remove the grease and impurities on the surface of 35CrMo steel hardware. Degreasing can be done by mechanical removal and chemical removal. The mechanical removal efficiency is low, and the surface of 35CrMo steel hardware is easily damaged during mechanical removal. The present invention uses chemical removal, first cleaning with acetone for 3-5 min, and then using 100-120 g / L potassium hydroxide + 50-60 g / L sodium carbonate solution at a temperature of 60-75°C for cleaning for 10-12 min; then using deionized water ultrasonic cleaning for 4-6 min, the grease or dirt on the surface of 35CrMo steel hardware can be completely removed. Rust removal is also one of the important links in the surface pretreatment of 35CrMo steel hardware. During the transportation, storage and processing of 35CrMo steel, iron oxide and rust often appear on the surface, which will cause the surface of the steel plate to become rough, seriously affecting the effect of subsequent zinc infiltration. Rust removal can be achieved by mechanical removal and chemical removal. Mechanical rust removal is to physically remove rust, iron oxide and paint on the surface of the steel plate, while chemical rust removal is to soak the steel plate in a rust removal liquid so that the rust and oxide on its surface are dissolved in the liquid, and the steel plate is cleaned before the coating solidifies. The present invention uses a mechanical shot blasting method to mechanically shot blast and remove rust on the surface of 35CrMo steel hardware for 6-8 minutes, then ultrasonically clean it with deionized water for 2-3 minutes, and finally dehydrate it with anhydrous ethanol and dry it at 65-70°C for 35-50 minutes, then seal it for zinc infiltration treatment.

[0027] ② The sherardizing agent used for the surface sherardizing of 35CrMo steel hardware of the present invention is composed of 54.0-57.0% by mass of zinc powder, 20.0-23.0% of SiO2 powder, 3.0-3.5% of CeO2 powder, 5.0-6.0% of aluminum powder, 2.5-3.0% of nickel powder, 2.5-3.0% of chromium powder, 3.0-3.5% of magnesium powder, 2.5-2.8% of NH4Cl powder, and 2.5-3.0% of B4C powder; the particle size of zinc powder, SiO2 powder, magnesium powder, NH4Cl powder, nickel powder, chromium powder and B4C powder is 80-120 mesh; the size of CeO2 powder and aluminum powder is 50-80 nm.

[0028] The sherardizing agent of the present invention contains 3.0-3.5% CeO2 powder, and the size of CeO2 powder is 50-80 nm. The addition of nanometer CeO2 powder can accelerate the penetration of zinc element into the surface of 35CrMo steel hardware, increase the thickness of the sherardizing layer and the hardness of the sherardizing layer, and also have the positive effect of improving the corrosion resistance of the sherardizing layer. Adding 5.0-6.0% aluminum powder, 2.5-3.0% nickel powder, 2.5-3.0% chromium powder and 3.0-3.5% magnesium powder in mass fraction to the sherardizing agent can further improve the corrosion resistance of the sherardizing layer. In particular, adding 2.5-3.0% B4C powder and 2.5-3.0% chromium powder in mass fraction to the sherardizing agent can easily generate a Cr2B phase with high hardness in the sherardizing layer, thereby improving the hardness and wear resistance of the sherardizing layer. Adding high melting point SiO2 powder with a mass fraction of 20.0-23.0% to the sherardizing agent is mainly used to prevent the zinc powder from bonding with the surface of 35CrMo steel fittings during the sherardizing process. Adding NH4Cl powder with a mass fraction of 2.5-2.8% to the sherardizing agent is also used. NH4Cl is an activator, and its main function is to activate zinc and the surface of 35CrMo steel fittings and promote the sherardizing process.

[0029] The sherardizing agent is evenly spread on the bottom of the sherardizing tank, and is pressed and compacted. The thickness of the sherardizing agent is 15-20 mm. A 35CrMo steel fitting whose surface has been pre-treated in step ① is placed on it. The sherardizing tank consists of a tank body, a sealing ring and a tank cover. The tank body and the tank cover are made of 1Cr18Ni9Ti stainless steel, and the sealing ring is made of red copper wrapped with aluminum foil. The sherardizing agent is then covered on the pre-treated 35CrMo steel fitting, and is pressed and compacted. Finally, the sherardizing tank is sealed. ③Put the sealed zincizing tank in step ② into a box-type resistance furnace, heat it to 410-415 ℃, control the heating rate at 60-80 ℃ / h, keep it warm for 1.5-2.0 h, then cut off the power and cool it to 350-360 ℃, and continue to keep it warm for 7-8 h; finally, turn off the power and cool it to 180-200 ℃ with the furnace, open the resistance furnace door and continue to cool it further. When the temperature drops below 150 ℃, take out the zincizing tank and cool it naturally to room temperature to complete the zincizing.

[0030] Since NH4Cl in the sherardizing agent is easily decomposed by heat, the generated hydrogen chloride gas and ammonia gas will overflow from the tank, making the sherardizing agent loose. When the gas overflows, the air outside the tank will enter the tank, causing the surface of the 35CrMo steel hardware and the sherardizing agent to oxidize. Therefore, the sherardizing tank must be well sealed. The present invention puts the sealed sherardizing tank into a box-type resistance furnace, heats it to 410-415 ℃, and controls the heating rate at 60-80 ℃ / h. The heating rate is slow, and the ammonium chloride (NH4Cl) decomposes slowly, so the expected reducing atmosphere will not be destroyed. At the same time, the gas generated by the decomposition of ammonium chloride will squeeze the air in the tank out of the sherardizing tank, which can ensure that the surface of the hardware will not be oxidized. Since the melting point of zinc is low, only 419.5℃, the high-temperature insulation time of sherardizing is too long, zinc is easy to melt, and adheres to the surface of the 35CrMo steel hardware, which seriously affects the surface quality of the hardware. Therefore, the insulation time of the high temperature section is controlled to be 1.5-2.0h. In order to ensure the thickness of the zinc-diffused layer, the present invention heats at 410-415 ° C for 1.5-2.0 h, then cuts off the power and cools to 350-360 ° C, and continues to heat for 7-8 h. The present invention heats to 410-415 ° C, heats for 1.5-2.0 h, then cuts off the power and cools to 350-360 ° C, and continues to heat for 7-8 h, and also eliminates the internal stress of 35CrMo steel hardware during oil-cooling quenching, stabilizes the organization, and improves the toughness and plasticity of 35CrMo steel hardware.

[0031] The present invention aims to solve the problem that various current sherardizing technologies have thin sherardizing layer thickness and low sherardizing layer hardness, which leads to the problem that the surface of the electric hardware is very easy to fail under the combined action of corrosion and wind and sand wear after ordinary sherardizing treatment. By optimizing the sherardizing process, a sherardizing layer with large shearing layer thickness and high hardness is obtained on the surface of the electric hardware, thereby achieving the goal of extending the service life of the electric hardware.

[0032] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0033] Example 1 A method for zincizing an electric power connection fitting, the specific preparation process steps are as follows: ① First, heat the 35CrMo steel fittings to 830 ℃, keep them warm for 45 minutes, and then oil-quench them; then pre-treat the surface of the 35CrMo steel fittings after oil-quenching, including degreasing and rust removal; first clean them with acetone for 3 minutes, then use 100 g / L potassium hydroxide + 60 g / L sodium carbonate solution at 60 ℃ to clean them for 10 minutes; then use deionized water ultrasonic cleaning for 6 minutes, and use mechanical shot blasting to remove rust for 6 minutes; then use deionized water ultrasonic cleaning for 2 minutes; finally, dehydrate them with anhydrous ethanol and dry them at 65 ℃ for 50 minutes, then seal them for use; ② The sherardizing agent is composed of 57.0% zinc powder, 20.0% SiO2 powder, 3.5% CeO2 powder, 5.7% aluminum powder, 3.0% nickel powder, 2.5% chromium powder, 3.0% magnesium powder, 2.8% NH4Cl powder and 2.5% B4C powder by mass fraction; the particle size of zinc powder, SiO2 powder, magnesium powder, NH4Cl powder, nickel powder, chromium powder and B4C powder is 80-120 mesh; the size of CeO2 powder and aluminum powder is 50-80 nm; the sherardizing agent is evenly spread on the bottom of the sherardizing tank and compacted. The thickness of the sherardizing agent is 20 mm, and place the 35CrMo steel hardware whose surface has been pre-treated in step ① on it; the zinc-diffusion tank is composed of three parts: tank body, sealing ring and tank cover, where the tank body and tank cover are made of 1Cr18Ni9Ti stainless steel, and the sealing ring is made of red copper wrapped with aluminum foil; then cover the hardware with zinc-diffusion agent and press it tightly; finally, seal the zinc-diffusion tank; ③Put the sealed zinc-diffusion tank in step ② into a box-type resistance furnace, heat it to 415 ℃, control the heating rate at 80 ℃ / h, keep it warm for 1.5 hours, then cut off the power and cool it to 360 ℃, and keep it warm for 7 hours; finally, cut off the power and cool it to 200 ℃ with the furnace, open the resistance furnace door and continue to cool it further, and when the temperature drops below 150 ℃, take out the zinc-diffusion tank and cool it naturally to room temperature to complete the zinc-diffusion. The thickness of the zinc-diffusion layer on the surface of the 35CrMo steel hardware finally obtained reaches 162-169 µm, and the hardness of the zinc-diffusion layer reaches 492-505 HV.

[0034] Example 2 A method for zincizing an electric power connection fitting, the specific preparation process steps are as follows: ① First, heat the 35CrMo steel fittings to 850 ℃, keep them warm for 30 minutes, and then quench them with oil. Then, pretreat the surface of the 35CrMo steel fittings after oil quenching, including degreasing and rust removal. First, clean them with acetone for 5 minutes, then use 120 g / L potassium hydroxide + 50 g / L sodium carbonate solution at 75 ℃ for 12 minutes, then use deionized water ultrasonic cleaning for 4 minutes, and use mechanical shot blasting to remove rust for 8 minutes, then use deionized water ultrasonic cleaning for 3 minutes, finally dehydrate with anhydrous ethanol and dry at 70 ℃ for 35 minutes, then seal and set aside. ② The sherardizing agent is composed of 54.0% zinc powder, 22.5% SiO2 powder, 3.0% CeO2 powder, 6.0% aluminum powder, 2.5% nickel powder, 3.0% chromium powder, 3.5% magnesium powder, 2.5% NH4Cl powder and 3.0% B4C powder by mass fraction; the particle size of zinc powder, SiO2 powder, magnesium powder, NH4Cl powder, nickel powder, chromium powder and B4C powder is 80-120 mesh; the size of CeO2 powder and aluminum powder is 50-80 nm; the sherardizing agent is evenly spread on the bottom of the sherardizing tank and compacted. The thickness of the sherardizing agent is 15 mm, and place the 35CrMo steel hardware whose surface has been pre-treated in step ① on it; the zinc-diffusion tank is composed of three parts: tank body, sealing ring and tank cover, where the tank body and tank cover are made of 1Cr18Ni9Ti stainless steel, and the sealing ring is made of red copper wrapped with aluminum foil; then cover the hardware with zinc-diffusion agent and press it tightly; finally, seal the zinc-diffusion tank; ③Put the sealed zinc-diffusion tank in step ② into a box-type resistance furnace, heat it to 410 ℃, control the heating rate at 60 ℃ / h, keep it warm for 2.0 h, then cut off the power and cool it to 350 ℃, and keep it warm for 8 h; finally, cut off the power and cool it to 180 ℃ with the furnace, open the resistance furnace door and continue to cool it further, and when the temperature drops below 150 ℃, take out the zinc-diffusion tank and cool it naturally to room temperature to complete the zinc-diffusion. The thickness of the zinc-diffusion layer on the surface of the 35CrMo steel hardware finally obtained reaches 163-168 µm, and the hardness of the zinc-diffusion layer reaches 488-497 HV.

[0035] Example 3 A method for zincizing an electric power connection fitting, the specific preparation process steps are as follows: ① First, heat the 35CrMo steel fittings to 840 °C, keep them warm for 35 minutes, and then oil-quench them; then pre-treat the surface of the 35CrMo steel fittings after oil-quenching, including degreasing and rust removal; first clean them with acetone for 4 minutes, then use 110 g / L potassium hydroxide + 55 g / L sodium carbonate solution at 65 °C to clean them for 11 minutes; then use deionized water ultrasonic cleaning for 5 minutes, and use mechanical shot blasting to remove rust for 7 minutes; then use deionized water ultrasonic cleaning for 2.5 minutes; finally, dehydrate them with anhydrous ethanol and dry them at 68 °C for 45 minutes, then seal them for use; ② The sherardizing agent is composed of 54.3% zinc powder, 23.0% SiO2 powder, 3.2% CeO2 powder, 5.0% aluminum powder, 2.9% nickel powder, 2.8% chromium powder, 3.3% magnesium powder, 2.7% NH4Cl powder, and 2.8% B4C powder; the particle size of zinc powder, SiO2 powder, magnesium powder, NH4Cl powder, nickel powder, chromium powder, and B4C powder is 80-120 mesh; the size of CeO2 powder and aluminum powder is 50-80 nm; the sherardizing agent is evenly spread on the bottom of the sherardizing tank and compacted. The thickness of the sherardizing agent is 18 mm, and place the 35CrMo steel hardware whose surface has been pre-treated in step ① on it; the zinc-diffusion tank is composed of three parts: tank body, sealing ring and tank cover, where the tank body and tank cover are made of 1Cr18Ni9Ti stainless steel, and the sealing ring is made of red copper wrapped with aluminum foil; then cover the hardware with zinc-diffusion agent and press it tightly; finally, seal the zinc-diffusion tank; ③Put the sealed zinc-diffusion tank in step ② into a box-type resistance furnace, heat it to 412 ℃, control the heating rate at 70 ℃ / h, keep it warm for 1.8 hours, then cut off the power and cool it to 355 ℃, and keep it warm for 7.5 hours; finally, cut off the power and cool it to 190 ℃ with the furnace, open the resistance furnace door and continue to cool it further, and when the temperature drops below 150 ℃, take out the zinc-diffusion tank and cool it naturally to room temperature to complete the zinc-diffusion. The thickness of the zinc-diffusion layer on the surface of the 35CrMo steel hardware finally obtained reaches 166-171 µm, and the hardness of the zinc-diffusion layer reaches 483-490 HV.

[0036] Example 4 A method for zincizing an electric power connection fitting, the specific preparation process steps are as follows: ① First, heat the 35CrMo steel fittings to 845 ℃, keep them warm for 40 minutes, and then oil-quench them; then pre-treat the surface of the 35CrMo steel fittings after oil-quenching, including degreasing and rust removal; first clean them with acetone for 4.5 minutes, then use 115 g / L potassium hydroxide + 58 g / L sodium carbonate solution at 70 ℃ to clean them for 11.5 minutes; then use deionized water ultrasonic cleaning for 4.5 minutes, and use mechanical shot blasting to remove rust for 7.5 minutes; then use deionized water ultrasonic cleaning for 2 minutes; finally, dehydrate them with anhydrous ethanol and dry them at 66 ℃ for 40 minutes, then seal them for use; ② The sherardizing agent is composed of 56.0% zinc powder, 21.0% SiO2 powder, 3.3% CeO2 powder, 5.5% aluminum powder, 2.8% nickel powder, 2.7% chromium powder, 3.2% magnesium powder, 2.6% NH4Cl powder, and 2.9% B4C powder by mass fraction; the particle size of zinc powder, SiO2 powder, magnesium powder, NH4Cl powder, nickel powder, chromium powder and B4C powder is 80-120 mesh; the size of CeO2 powder and aluminum powder is 50-80 nm; the sherardizing agent is evenly spread on the bottom of the sherardizing tank and compacted. The thickness of the sherardizing agent is 17 mm, and place the 35CrMo steel hardware whose surface has been pre-treated in step ① on it; the zinc-diffusion tank is composed of three parts: tank body, sealing ring and tank cover, where the tank body and tank cover are made of 1Cr18Ni9Ti stainless steel, and the sealing ring is made of red copper wrapped with aluminum foil; then cover the hardware with zinc-diffusion agent and press it tightly; finally, seal the zinc-diffusion tank; ③Put the sealed zinc-diffusion tank in step ② into a box-type resistance furnace, heat it to 412℃, control the heating rate at 65℃ / h, keep it warm for 1.8 hours, then cut off the power and cool it to 358℃, and keep it warm for 7.8 hours; finally, cut off the power and cool it to 195℃, open the resistance furnace door and continue to cool it further, and when the temperature drops below 150℃, take out the zinc-diffusion tank and cool it naturally to room temperature to complete the zinc-diffusion. The thickness of the zinc-diffusion layer on the surface of the 35CrMo steel hardware finally obtained reaches 166-170 µm, and the hardness of the zinc-diffusion layer reaches 485-494 HV.

[0037] The present invention overcomes the problems of unstable infiltration layer and long process cycle in the traditional powder sherardizing technology. The sherardizing time of the present invention is short, the thickness of the sherardizing layer is greater than 160 μm, and the hardness of the sherardizing layer is greater than 480 HV; the sherardizing layer has a dense structure, and the sherardizing layer is well combined with the surface of the 35CrMo steel hardware, ensuring that the sherardizing layer will not crack or peel off during the use of the hardware. In order to increase the thickness of the sherardizing layer in the traditional sherardizing, it is necessary to increase the sherardizing temperature to above 420°C, which exceeds the melting point of zinc and is in liquid phase, and accelerates the infiltration of liquid zinc into the metal surface to obtain the required sherardizing layer. However, the sherardizing agent is easy to adhere to the metal surface and is not easy to clean. The present invention accelerates the infiltration of zinc elements into the surface of the 35CrMo steel hardware by adding nano-CeO2, reduces the sherardizing temperature, shortens the sherardizing time, and has a good energy-saving effect. The sherardizing process of the present invention has no air pollution, no zinc vapor pollution, no zinc dust pollution, no acid water pollution, and no chromium water pollution, and is a clean sherardizing technology.

[0038] The zinc-diffused layer of the present invention has high hardness and excellent corrosion resistance and wear resistance. The corrosion abrasion wear test is carried out by using an MLS-225 rubber wheel wear tester. The sample size is 57 mm × 19 mm × 6 mm, the working surface size is 57 mm × 19 mm, and the particle size of the quartz sand used in the test is 40-70 mesh. The sample is installed so that the working surface of the sample is in close contact with the rubber wheel under the action of the load. During the experiment, a solution with a pH value of 14 is mixed with a silicon dioxide abrasive in a volume ratio of 3:1, and the test load is 210N. Under the same corrosion and wear conditions, the corrosion resistance and wear resistance of the zinc-diffused layer of the present invention is improved by more than 80% compared with the ordinary zinc-diffused layer, and is more than 3 times that of quenched 35CrMo steel. The present invention can significantly extend the service life of power fittings and has good prospects for promotion and application.

[0039] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

Claims

1. A zirconizing agent, characterized in that: Calculated by mass percentage, it includes 54.0-57.0% zinc powder, 20.0-23.0% SiO2 powder, 3.0-3.5% CeO2 powder, 5.0-6.0% aluminum powder, 2.5-3.0% nickel powder, 2.5-3.0% chromium powder, 3.0-3.5% magnesium powder, 2.5-2.8% NH4Cl powder and 2.5-3.0% B4C powder.

2. The zirconizing agent according to claim 1, characterized in that: The particle size of zinc powder, SiO2 powder, magnesium powder, NH4Cl powder, nickel powder, chromium powder and B4C powder is 80-120 mesh.

3. The zirconizing agent according to claim 1, characterized in that: The sizes of CeO2 powder and aluminum powder are 50-80 nm.

4. A method for sherardizing an electric power connection fitting, characterized in that: The following steps are involved: The steel fittings are austenitized and then cooled; Pre-treating the surface of the cooled steel fittings; The pretreated steel fittings and the sherardizing agent according to any one of claims 1 to 3 are added into a closed sherardizing tank, kept warm at a set temperature, and then cooled in stages.

5. The method for sherardizing electric power connection fittings according to claim 4, characterized in that: The austenitizing temperature is 830-850°C and the time is 30-45 minutes.

6. The method for sherardizing electric power connection fittings according to claim 4, characterized in that: After the steel fittings are austenitized, they are cooled and oil quenched.

7. The method for sherardizing electric power connection fittings according to claim 4, characterized in that: The set temperature is 410-415℃ and the holding time is 1.5-2.0 h.

8. The method for sherardizing electric power connection fittings according to claim 4, characterized in that: The temperature was raised to the set temperature at a rate of 60-80 ℃ / h.

9. The method for sherardizing electric power connection fittings according to claim 4, characterized in that: The specific stage cooling is: first at 350-360℃, keep warm for 7-8 hours, then cool to 180-200℃ with the furnace, and then naturally cool to room temperature.

10. The method for sherardizing electric power connection fittings according to claim 4, characterized in that: The cooled steel fittings are surface-pretreated, including degreasing and rust removal.

11. An anti-corrosion power connection fitting, characterized in that: The method is prepared by any one of claims 4 to 13.

12. The anti-corrosion power connection fitting according to claim 11, characterized in that: The invention comprises an electric connection fitting and a sherardizing layer on the surface of the electric connection fitting, wherein the thickness of the sherardizing layer is 162-171 µm and the hardness of the sherardizing layer is 483-505 HV.

Citation Information

Patent Citations

  • Method for preparing zinc-aluminum-magnesium powder zincizing agent and treating steel

    CN111926285A